Shaping travels and land use with bus rapid transit: a developed city's visualisation with smartcard and census data. Issue 1 (1st January 2016) - Zhou, Jiangping; Sipe, Neil; Mateo-Babiano, Iderlina; Rowe, Warren
Abstract: Transit and land-use integration is regarded as one of the most important means of avoiding or reducing car dependence and urban sprawl, which are thought as major culprits of unsustainability. In developing countries, rail rapid transit could be too expensive to become the predominant component of their respective systems. However, bus rapid transit (BRT) as one of the cheapest forms of mass transit is a better alternative for those countries. In developing countries, BRT has transformed numerous cities such as Curitiba, Brazil; Bogota, Columbia; and Guangzhou, China. Can BRT have the same transformative impacts for cities in developed countries as well? Can the impacts of BRT be visualized using the transit population? Given that few cities in developed countries have BRT and ridership data of BRT are not always available, the above questions have not been well addressed before. To answer these two questions, we analysed smartcard swipes over a five-day weekday period (11–15 March 2013) for Brisbane in Queensland, Australia, and reconstructed trip trajectories of those 255, 887 transit riders. We found that BRT serves a significant percentage and number of travellers, thus shaping travel behaviour and ultimately land use – when transit ridership and rate of transit usage are used as indicators. This is a significant achievement in Australia, a country known for its car dependence and urban sprawl.